PERSEPSI FOTOGRAFER PROFESIONAL DALAM PEMAKNAAN FOTO KONSEPTUAL KARYA DARWIS TRIADI DI BUKU “EMOSI SEBUAH FOTO” - Zufar Alrozan; Ageng Soeharno (SS&H: Studies in Social Sciences and Humanities, 2025)
This study aims to determine the perceptions of professional photographers in interpreting conceptual photographs by Darwis Triadi in the book "Emotions of a Photo." In addition, this study also seeks to understand the meaning contained in the images by analyzing the visual and artistic elements displayed in the work. The study uses a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. Interviews were conducted with five professional photographers in Jember Regency as sources who have experience in the field of conceptual photography. The results of the study indicate that conceptual photography is a form of photography that starts from an idea or concept that is carefully designed before the image is taken. The photographers consider that Darwis Triadi's photographs are full of strong emotional, symbolic, and visual aesthetic messages. The process of interpreting the photos is carried out through interpretation of visual elements such as lighting, model poses, colors, and composition. This study also found that factors of experience, visual references, and the photographer's background also influence the perception of the meaning of the photo. Thus, this study contributes to understanding how professional perceptions are formed in reading and interpreting conceptual photography works as a form of complex visual communication.